Shareholder protection in close corporations : theory, operation, and application of shareholder withdrawal - Koh, Alan K (Cambridge : Cambridge University Press, 2022)
Close corporations, which are legal forms popular with small and medium enterprises, are crucial to every major economy's private sector. However, unlike their 'public' corporation counterparts, close corporation minority shareholders have limited exit options, and are structurally vulnerable in conflicts with majority or controlling shareholders. 'Withdrawal remedies'-legal mechanisms enabling aggrieved shareholders to exit companies with monetary claims-are potent minority shareholder protection mechanisms. This book critically examines the theory and operation of withdrawal remedies in four jurisdictions: the United States, the United Kingdom, Germany, and Japan. Developing and applying a theoretical and comparative framework to the analysis of these jurisdictions' withdrawal remedies, this book proposes a model withdrawal remedy that is potentially applicable to any jurisdiction. With its international, functional, and comparative analysis of withdrawal remedies, it challenges preconceptions about shareholder remedies and offers a methodology for comparative corporate law in both scholarship and practice.
Title from publisher's bibliographic system (viewed on 14 Oct 2022).
Keywords: Close corporations -- Finance; Stockholders -- Legal status, laws, etc; Corporations -- Investor relations